From social harm to zemiology a critical introduction - Canning, Victoria; Tombs, Steve (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
This book outlines key developments in understanding social harm by setting out its historical foundations and the discussions which have proliferated since. It examines various attempts to conceptualise social harm and highlights key sites of contestation in its relationship to criminology to argue that these act as the basis for an activist zemiology, one directed towards social change for social justice. The past two decades have seen a proliferation of debate related to social harm in and around criminology. From climate catastrophe and a focus on environmental harms, unprecedented deaths generating focus on border harms and the coronavirus pandemic revealing the horror of mass and arguably avoidable deaths across the globe, critical studies in social harm appear ever more pressing. Drawing on a range of international case studies of cultural, emotional, physical and economic harms, From Social Harm to Zemiology locates the study of social harm in an accessible fashion. In doing so it sets out how a zemiological lens can moves us beyond many of the problematic legacies of criminology. This book rejects criminologies which have disproportionately served to regulate intersectional groups, and which have arguably inflicted as much or more harm by bolstering the very ideologies of control in offering minor reforms that inadvertently expand and strengthen states and corporations. It does this by sketching out the contours, objects, methods and ontologies of a disciplinary framework which rejects commonplace assumptions of value freedom'. From Social Harm to Zemiology advocates social change in accordance with groups who are most disenfranchised, and thus often most socially harmed. An accessible and compelling read, this book is essential reading for all zemiologists, critical criminologists, and those engaged with criminological and social theory.
Understanding social harm -- Towards social harm and zemiology -- A provisional typology of harm -- The relations and ontologies of harm -- Doing zemiology -- Conclusion: activist zemiology for social justice.
OCLC-licensed vendor bibliographic record.
Keywords: Critical criminology; Crime -- Sociological aspects; Social justice; SOCIAL SCIENCE / Criminology